Impact of Pulmonary Function Measurements on Long-Term Survival After Lobectomy for Stage I Non-Small Cell Lung Cancer - Berry, Mark F. (Ann Thorac Surg, 2015)
BACKGROUND: Pulmonary function tests predict respiratory complications after lobectomy. We evaluated the impact of pulmonary function measurements on long-term survival after lobectomy for stage I non-small cell lung cancer. METHODS: The relationship between percent predicted Forced Expiratory Volume in one second (FEV1) and percent predicted Diffusing Capacity of the Lung for Carbon Monoxide (DLCO) and overall survival for patients who underwent lobectomy without induction therapy for stage I (T1-2N0M0) non-small cell lung cancer from 1996–2012 was evaluated using the Kaplan-Meier approach and a multivariable Cox proportional hazard model. RESULTS: During the study period, 972 patients (mean DLCO 76±21, mean FEV1 73±21) met inclusion criteria. Peri-operative mortality was 2.6% (n=25). The 5-year survival of the entire cohort was 60.1% with a median follow-up of 43 months. The five-year survival for patients with percent predicted FEV1 stratified by > 80%, 61–80%, 41–60%, and ≤ 40% was 70.1%, 59.3%, 52.5%, and 53.4% respectively. The five-year survival for patients with percent predicted DLCO stratified by > 80%, 61–80%, 41–60%, and ≤ 40% was 70.2%, 63.4%, 44.2%, and 33.1% respectively. In multivariable survival analysis, both larger tumor size (hazard ratio 1.15, p=0.01) and lower DLCO (hazard ratio 0.986, p<0.0001) were significant predictors of worse survival. The association of FEV1 and survival was not statistically significant (p=0.18). CONCLUSIONS: Survival after lobectomy for patients with stage I non-small cell lung cancer is impacted by lower DLCO, which can be used in the risk/benefit assessment when choosing therapy.